Enterprise grid computing with Oracle - Goyal, Brajesh (McGraw-Hill, 2006)
This book is an excellent source of pragmatic guidance on how users can realize real benefits from adopting Grid Computing today while addressing their pressing business needs and leveraging their current IT investments." --Thomas Kurian, Senior Vice President, Oracle Server Technologies